The parish priests in economy of nuestra señora de la Limpia Concepcion from Canta, 16th and 17th Centuries - León Fernandez, Dino (2009)
Pastors of the doctrine of Canta appear as a special economic activity surprise, going back several years ago. The Priests canteños functioned as effective extraction of surplus indigenous, appropriate for several extra ways or mechanisms, and incorporating the most part, the expansive colonial urban market, while also producing for domestic consumption in the community. Moreover, this work is a sample of cases conducted by the Indian doctrine of Canta, during the seventeenth century, against its priests.